Fall-related mortality trends in Australia and the United Kingdom: Implications for research and practice. (December 2020) - Wu, Harry; Mach, John; Le Couteur, David G.; Hilmer, Sarah N.
Highlights: To our knowledge, this is the first study to examine long-term nationwide age- and sex-specific trends in falls mortality in more than one country. Reported fall-related deaths increased from 2006 to 2016 in Australia and the UK. There were distinct age and sex differences in mortality trends. Death rates from falls increased with age. People aged ≥ 95 years had the highest mortality rate from falls. Fall-related mortality rates declined in younger people and increased in older people over the study period in both countries. Mortality from falls was higher in men, but it increased at a faster rate in women. Abstract: Objectives: To characterise changes in nationwide fall-related mortality rates in Australia and the United Kingdom (UK) between 2006 and 2016 by age group and sex. Study design: Trend analysis of falls mortality data from World Health Organization (WHO) Mortality Database for the Australian and UK population. Main outcome measures: We assessed age-specific, sex-specific and age-adjusted mortality rates. Mortality trends were assessed via the annual percentage change (APC) using joinpoint regression. Results: The annual average age-adjusted falls mortality rate was 38.63 per 1, 000, 000 population in Australia, and 34.12 per 1, 000, 000 population in the UK. From 2006 to 2016, age-adjusted mortality rate due to falls increased in Australia and the UK by an average annual rate of 3.77% (95% CI 2.91% to 4.64%; p<0.01) and 2.11% (95% CI 1.43% to 2.80%; p<0.01) respectively. Death rates from falls increased with age. People aged ≥95 years had the highest mortality rate from falls in Australia and the UK. Men had a higher annual average age-adjusted mortality rate from falls than women (1.6 times higher in Australia and 1.7 times higher in the UK). Women had a larger annual percentage increase in falls mortality rate compared to men over the study period. Conclusions: There was a major increase in reported fall-related deaths in Australia and the UK between 2006 and 2016, especially in the very elderly. Men had a higher mortality rate from falls than women. Factors contributing to the apparent increases in fall-related mortality may include reduced cancer and cardiovascular mortality and better ascertainment of cause of death.